The big five personalities traits and job performance of employees in the FMCG sector in Selangor - Pavityrah, Mokhan (2023)
In order for a business to successfully survive and compete with other competitors in today's fragile economic environment, proactive and committed personnel must perform greater standards of job performance. One of the key components that provide both objectives and strategies to fulfill the corporate mission is the performance of employees on the job. Hence, the purpose of this research was to examine how the Big Five Personality traits of employees on the job performance in the FMCG sector in Selangor. The study sampled 276 people from the FMCG sector in Selangor using convenience sampling method and the study's subjects were the employees. The tool for gathering data was a questionnaire. According to the study, Agreeableness, Openness to experience and Conscientiousness positively and significantly impacted job performance. Extraversion and Neuroticism/Emotional Stability, on the other hand, had a weak and insignificant relationship with job performance. According to the study's findings, people that exhibit high levels of Agreeableness, Openness to experience, and Conscientiousness are more likely to succeed in their job performances. The findings were then discussed, and recommendations were made. Finally, the researcher presented the conclusions in order to conclude the entire study.